A fiber-reinforced porous phosphorus removal composite carrier, a preparation method thereof, a phosphorus-containing water treatment method, and a utilization method of the composite carrier after absorbing phosphorus

CN122937764APending Publication Date: 2026-10-20CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611320629.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

在部分处理工艺中,吸磷材料需要经过脱附和再生后才能再次使用,增加了后续处理步骤;若将吸磷材料直接废弃,则其中富集的磷未能得到进一步利用

Benefits of technology

[0036](1)本发明将含铁活性组分的膨胀蛭石固定于海藻酸钙凝胶连续相中,形成具有一定尺寸和整体形态的复合载体,使处理完成后的载体能够从水体中分离。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention discloses a fiber-reinforced porous phosphorus removal composite carrier and its preparation method, a method for treating phosphorus-containing water, and a method for utilizing the composite carrier after phosphorus absorption. The composite carrier includes a carrier body with internal pores and a surface treatment layer. The carrier body includes a continuous phase of calcium alginate gel, expanded vermiculite containing iron-containing active components dispersed therein, and coconut fiber. During preparation, the components are mixed, pre-formed, cross-linked with calcium ions, and surface-treated to obtain an integral carrier. The resulting integral composite carrier is used for treating phosphorus-containing water. After phosphorus absorption, it can be separated from the treated water and can enter the soil utilization system without special desorption or regeneration treatment to regulate the migration behavior of phosphorus enriched by the carrier in the soil environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a phosphorus removal carrier and its preparation method, a water treatment method, and a carrier utilization method, particularly to a fiber-reinforced porous phosphorus removal composite carrier and its preparation method, a phosphorus-containing water treatment method, and a method for utilizing the composite carrier after phosphorus absorption. Background Technology

[0002] Phosphorus is a significant contributing factor to eutrophication. Domestic sewage, aquaculture wastewater, agricultural drainage, and some industrial wastewater may contain certain concentrations of phosphorus. If these pollutants enter natural water bodies without effective treatment, they can easily lead to excessive algae growth and deterioration of the aquatic ecosystem. Therefore, treating and recovering phosphorus from phosphorus-containing water bodies is of practical significance.

[0003] Currently, the main methods for treating phosphorus-containing water include chemical precipitation, biological treatment, membrane separation, and adsorption. Adsorption methods are characterized by relatively mild operating conditions, strong process adaptability, and ease of integration with other treatment units. Active materials with phosphorus-binding capabilities can be used to capture phosphorus in water, while mineral materials can serve as a loading matrix for active components to improve their dispersion and fixation.

[0004] Powdered or fine-particle adsorbents are easily dispersed in water during use, and typically require filtration, sedimentation, or other solid-liquid separation methods for recovery after treatment. The smaller the particle size, the more difficult the separation and repeated collection become. To improve the recyclability of adsorbents, gels or other molding materials can be used to immobilize the adsorbent components into a monolithic carrier of a certain size. However, immobilizing the adsorbent components in a monolithic carrier may limit the extent to which water can enter the carrier and contact the internal adsorbent components. Creating pores within the carrier can improve the conditions for water entry, but increased porosity may also reduce the carrier's structural integrity during immersion, leading to deformation, cracking, fragmentation, or surface material loss. Conversely, increasing the carrier's density, while beneficial for maintaining its overall shape, may further restrict the contact between water and the internal adsorbent components.

[0005] Therefore, a monolithically molded phosphorus removal carrier needs to balance its ability to enter water bodies and its ability to maintain its wet state. Simply increasing the porosity or simply increasing the density of the gel is insufficient to simultaneously meet the requirements of utilizing the internal adsorbed components and recovering the entire product after treatment.

[0006] Furthermore, the material after phosphorus adsorption is enriched with a certain amount of phosphorus. In some treatment processes, the phosphorus adsorption material needs to be desorbed and regenerated before it can be reused, which increases the number of subsequent treatment steps; if the phosphorus adsorption material is discarded directly, the enriched phosphorus cannot be further utilized. Therefore, it is necessary to provide a phosphorus removal carrier that can be completely separated from the treated water and can enter the subsequent utilization system without special phosphorus desorption or adsorbent regeneration treatment. Summary of the Invention

[0007] Purpose of the invention: The purpose of this invention is to provide an integrally molded fiber-reinforced porous phosphorus removal composite carrier, which improves the contact between the water body and the phosphorus capture components inside the carrier, enhances the carrier's ability to maintain its morphology in the aquatic environment, and enables the composite carrier to be completely separated from the treated water body after phosphorus absorption, thus providing conditions for the recycling of the phosphorus-absorbing carrier and its application in the soil.

[0008] The second objective of this invention is to provide a method for preparing the aforementioned fiber-reinforced porous phosphorus removal composite carrier;

[0009] A third objective of this invention is to provide a method for treating phosphorus-containing water.

[0010] The third objective of this invention is to provide a method for utilizing a composite carrier after phosphorus absorption.

[0011] Technical Solution: The fiber-reinforced porous phosphorus removal composite carrier of the present invention includes a carrier body with internal pores and a surface treatment layer formed on the outer surface of the carrier body; the carrier body includes a calcium alginate gel continuous phase, expanded vermiculite containing iron active components, and coconut fiber; the calcium alginate gel continuous phase is used to fix the expanded vermiculite containing iron active components and coconut fiber into an integral carrier; the expanded vermiculite containing iron active components is dispersed and fixed in the calcium alginate gel continuous phase for capturing phosphorus in water; the coconut fiber is distributed in the calcium alginate gel continuous phase for improving the internal skeleton retention ability of the carrier after immersion; the internal pores are formed in the carrier body to increase the opportunity for water to enter the interior of the carrier and come into contact with the expanded vermiculite containing iron active components; the surface treatment layer is formed by treating the carrier body with methylcellulose solution and drying it to reduce the loss of surface material of the carrier during immersion in the water environment and improve the overall morphological retention ability of the carrier after immersion.

[0012] The iron-containing active component is formed and loaded on the surface and / or pore region of expanded vermiculite; the iron-containing active component is formed by the reaction of an iron-containing precursor under alkaline conditions. The iron-containing precursor includes an iron salt; the iron salt is preferably ferric nitrate.

[0013] The calcium alginate gel continuous phase is formed by cross-linking sodium alginate with calcium ions; the calcium ions are provided by a calcium-containing cross-linking agent; the calcium-containing cross-linking agent is preferably calcium chloride.

[0014] The coconut fiber and the calcium alginate gel continuous phase together form the fiber-reinforced structure inside the carrier.

[0015] The internal pores are formed by the reaction of magnesium carbonate and citric acid to produce gas; the magnesium carbonate and citric acid react during the preforming and / or curing process of the carrier to form pores inside the molded slurry.

[0016] The surface treatment layer is a methylcellulose surface treatment layer; the methylcellulose surface treatment layer is formed after the carrier completes calcium ion crosslinking.

[0017] The composite carrier is an integral carrier that can be directly separated from the treated water body.

[0018] The preparation method of the above-mentioned fiber-reinforced porous phosphorus removal composite carrier includes the following steps:

[0019] (1) Mix the iron-containing precursor with expanded vermiculite to form and load the iron-containing active component on the surface and / or pore area of ​​the expanded vermiculite. After solid-liquid separation, the expanded vermiculite containing the iron-containing active component is obtained.

[0020] (2) Mix expanded vermiculite containing iron active components with coconut fiber, so that the coconut fiber is distributed in the mixture to obtain fiber-reinforced mixture;

[0021] (3) Add sodium alginate solution, magnesium carbonate and citric acid to the fiber-reinforced mixture and mix to form a molding slurry; magnesium carbonate and citric acid react during mixing, preforming and / or curing to generate gas, thereby forming pores inside the molding slurry;

[0022] (4) Place the molding slurry obtained in step (3) into a mold for pre-forming treatment to obtain a pre-formed body; place the pre-formed body into a calcium-containing cross-linking agent solution for cross-linking, so that sodium alginate forms a continuous phase of calcium alginate gel, and the expanded vermiculite, coconut fiber and internal pores containing iron active components are kept in the overall molding carrier.

[0023] (5) The integrally molded carrier obtained in step (4) is surface treated with methylcellulose solution and then dried to form a methylcellulose surface treatment layer on the outer surface of the carrier, thereby obtaining the fiber-reinforced porous phosphorus removal composite carrier.

[0024] In step (1), the iron-containing precursor solution is adjusted to alkaline, and a dispersant and expanded vermiculite are added. After dispersion and heating reaction, the iron-containing active component is formed and loaded onto the expanded vermiculite. After the reaction is completed, the obtained solid is washed and dried to obtain expanded vermiculite containing the iron-containing active component.

[0025] The phosphorus-containing water treatment method of the present invention includes the following steps:

[0026] The fiber-reinforced porous phosphorus removal composite carrier described above is placed in a phosphorus-containing water body, allowing the phosphorus-containing water body to enter the composite carrier and come into contact with the expanded vermiculite containing iron active components, thereby capturing phosphorus in the water body;

[0027] After treatment, the phosphorus-absorbed composite carrier is separated from the treated water.

[0028] The composite carrier is placed in phosphorus-containing water in the form of a complete carrier, a block carrier, or other integral form that facilitates solid-liquid separation.

[0029] The method for utilizing the phosphorus-absorbing composite carrier described in this invention includes the following steps:

[0030] The composite carrier that has absorbed phosphorus by the above method is separated from the treated water body, and the separated composite carrier is added to the soil utilization system.

[0031] The composite carrier that has absorbed phosphorus does not undergo special phosphorus desorption treatment or adsorbent regeneration treatment before entering the soil utilization system.

[0032] The soil utilization system is used to facilitate the migration of phosphorus enriched in the composite carrier within the soil environment.

[0033] Among them, by adjusting the concentration of sodium alginate solution and / or the surface treatment conditions of methylcellulose, the migration process of phosphorus in the composite carrier after phosphorus absorption in the soil environment can be changed; the continuous phase of calcium alginate gel formed by calcium ion cross-linking can affect the migration behavior of phosphorus enriched in the carrier.

[0034] Invention Principle: In integrally molded phosphorus removal carriers, increasing internal pores facilitates water entry into the carrier and contact with phosphorus-capturing components. However, the formation of pores may reduce the carrier's ability to maintain its shape in an aquatic environment. While increasing the carrier's density helps maintain its overall shape, it may limit the contact between water and the internal phosphorus-capturing components. Therefore, this invention incorporates phosphorus-capturing components, reinforcing fibers, and internal pores into an integrally molded gel carrier, and performs surface treatment on the molded carrier to improve the carrier's phosphorus-capturing capacity and water entry conditions while maintaining its shape retention after immersion.

[0035] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects:

[0036] (1) In this invention, expanded vermiculite containing iron active components is fixed in the continuous phase of calcium alginate gel to form a composite carrier with a certain size and overall shape, so that the carrier after treatment can be separated from the water.

[0037] (2) This invention uses expanded vermiculite containing iron active components as the phosphorus capture component, and improves the fixation stability of the iron-containing components by loading the active components, which is beneficial to improving the phosphorus capture capacity of the composite carrier. The experimental results show that, compared with the direct physical mixing method, the introduction of iron-containing active components by loading can reduce the release of iron components during the soaking process and improve the utilization stability of the active components.

[0038] (3) The present invention utilizes the reaction of magnesium carbonate and citric acid to form internal pores, and improves the conditions for water to enter the carrier by adjusting the amount of pore-forming components. The experimental results show that appropriate pore-forming can improve phosphorus removal rate and phosphorus enrichment capacity, while excessive pore-forming further increases the degree of pore-forming, although it improves the water entry capacity, but fails to further improve phosphorus removal performance and may affect the carrier's ability to maintain wet structure.

[0039] (4) In this invention, coconut fiber is set in the continuous phase of calcium alginate gel and combined with methyl cellulose surface treatment to improve the structural retention ability of porous carrier after immersion and reduce surface material loss. Compared with composite carrier using wood pulp fiber, the use of coconut fiber can further improve the morphological retention ability of carrier in wet environment.

[0040] (5) The composite carrier obtained by this invention can be separated from the treated water after phosphorus adsorption and can enter the soil environmental utilization system without special phosphorus desorption or adsorbent regeneration treatment. The experimental results show that some of the phosphorus enriched by the carrier can migrate into the soil as the cultivation time is extended and be converted into an extractable form of NaHCO3, which provides an implementation method for the subsequent resource utilization of the carrier after phosphorus adsorption. Attached Figure Description

[0041] Figure 1 This is a schematic diagram of the structure of the fiber-reinforced porous phosphorus removal composite carrier of the present invention;

[0042] Figure 2 This is a photograph of the fiber-reinforced porous phosphorus removal composite carrier obtained in Example 1 of the present invention. Detailed Implementation

[0043] The present invention will now be described in further detail.

[0044] Example 1

[0045] A method for preparing a fiber-reinforced porous phosphorus removal composite carrier includes the following steps:

[0046] (1) Preparation of expanded vermiculite containing iron active components

[0047] Weigh 20.2 g of ferric nitrate nonahydrate and prepare 100 mL of 0.5 mol / L ferric nitrate solution using deionized water. Adjust the pH of the resulting system to 11.5 using sodium hydroxide solution, then add 0.10 g of sodium polyacrylate and stir until uniformly dispersed. Add 50 g of expanded vermiculite to the above system, mix, and ultrasonically disperse for 1 h. React at 70 ℃ with continuous stirring for 24 h to allow the iron-containing active component to form and be loaded onto the surface and / or pore regions of the expanded vermiculite. After the reaction, perform solid-liquid separation, washing the obtained solid with deionized water until the last wash solution is neutral. Dry the washed solid at 60 ℃ for 12 h to obtain expanded vermiculite containing the iron-containing active component.

[0048] (2) Preparation of fiber-reinforced mixtures

[0049] Weigh 55 g of expanded vermiculite containing the iron-containing active component obtained in step (1) and 15 g of coconut fiber, and mix them evenly to obtain a fiber-reinforced mixture. The coconut fiber is distributed in the subsequently formed calcium alginate gel continuous phase to improve the internal skeleton retention ability of the composite carrier after immersion. The length of the coconut fiber ranges from 3 to 5 mm. The coconut fiber is dried and cut before use.

[0050] (3) Preparation of molding slurry

[0051] Add 250 mL of 2% sodium alginate solution to the fiber-reinforced mixture obtained in step (2), and mix until all solid components are evenly dispersed in the sodium alginate solution. Then add 10 g of magnesium carbonate, stir thoroughly, and then add 10 g of citric acid. Stir rapidly at room temperature for 1–3 min, and then immediately inject the resulting molding slurry into the mold, completing the molding process within 5 min.

[0052] (4) Preforming and calcium ion crosslinking

[0053] The molding slurry obtained in step (3) is injected into a spherical silicone mold. The diameter of the molding cavity of the spherical silicone mold is 30 mm. About 12-15 g of molding slurry is added to each molding cavity, ensuring that the molding slurry basically fills the molding cavity without obvious overflow. The mold containing the molding slurry is pre-molded at 50 ℃ for 2 h to allow the molding slurry to maintain the predetermined shape, resulting in a wet preform. The obtained wet preform is removed from the mold and completely immersed in a 5% (w / w) calcium chloride solution. It is cross-linked at room temperature for 30 min to allow sodium alginate to cross-link with calcium ions to form a continuous calcium alginate gel phase. After cross-linking is completed, the carrier is removed from the calcium chloride solution and the surface solution is drained off to obtain the integrally molded carrier.

[0054] (5) Surface treatment of methylcellulose

[0055] Take the integral molded carrier obtained in step (4), and completely immerse it in a sufficient amount of 1% methylcellulose solution for 30 min. After soaking, remove the carrier, drain off the excess solution on the surface, and dry it to constant weight under room temperature and ventilation conditions.

[0056] Figure 1 This is a schematic diagram of the structure of the fiber-reinforced porous phosphorus removal composite carrier of the present invention. In the diagram, 1 is the methylcellulose surface treatment layer, 2 is the calcium alginate gel continuous phase, 3 is expanded vermiculite containing iron active components, 4 is coconut fiber, and 5 is the internal pores.

[0057] Figure 2 This is a photograph of the fiber-reinforced porous phosphorus removal composite carrier obtained in Example 1 of the present invention; Figure 2 It can be seen that the prepared composite carrier has an integral spherical structure with a certain mechanical integrity, and the surface remains continuous without obvious cracking or pulverization, indicating that the preparation method of the present invention can obtain an integral composite carrier with good formability.

[0058] Example 2

[0059] The preparation method of this embodiment is basically the same as that of Example 1, except that in step (3), the amount of magnesium carbonate added is adjusted from 10 g to 15 g, and the amount of citric acid added is adjusted from 10 g to 15 g.

[0060] The resulting composite carrier was used to compare the changes in phosphorus removal rate and phosphorus enrichment per unit mass in water under varying pore-forming component dosage conditions, in order to determine the influence of pore-forming component dosage on the carrier's mass transfer capacity and phosphorus removal performance.

[0061] Example 3

[0062] The preparation method of this embodiment is basically the same as that of Example 1, except that in step (2), the amount of coconut fiber added is adjusted from 15 g to 20 g.

[0063] The resulting composite carrier was used to compare the change in the mass retention rate on the sieve after soaking under varying coconut fiber dosage conditions.

[0064] Example 4

[0065] The preparation method of this embodiment is basically the same as that of Example 1, except that: in step (3), the mass fraction of sodium alginate solution is adjusted from 2% to 3%; in step (5), the mass fraction of methylcellulose solution is adjusted from 1% to 2%.

[0066] The resulting composite carrier was used to compare the changes in the apparent extractable phosphorus ratio of phosphorus uptake test samples in a simulated soil system after adjusting the concentration of gel-forming components and surface treatment conditions simultaneously.

[0067] Example 5

[0068] The types and amounts of raw materials used in this embodiment, as well as steps (1) to (3), are the same as in Example 1. The difference is:

[0069] The molding slurry obtained in step (3) was injected into the same spherical silicone mold as in Example 1, and pre-molded at 50 °C for 2 h to obtain a wet pre-molded body.

[0070] The obtained wet preform was removed from the mold and completely immersed in a 5% (w / w) calcium chloride solution, and crosslinked at room temperature for 30 min. After crosslinking was completed, the carrier was removed, and the surface solution was drained off to obtain a calcium ion crosslinked integral molded carrier.

[0071] The obtained calcium ion cross-linked monolithic carrier was cut into small pieces of similar size. Based on the conversion relationship between wet and dry mass measured from parallel samples of the same batch, a 1% methylcellulose solution was applied at a rate of 0.20 mL per gram of dry mass. After coating, the mixture was allowed to stand for 30 min and then dried to constant weight under room temperature and ventilation conditions, resulting in a calcium ion cross-linked composite carrier with coating-based surface treatment.

[0072] The composite carrier obtained in this embodiment was used to compare with Comparative Example 5 to evaluate the effect of calcium ion crosslinking on phosphorus migration behavior in the soil of the phosphorus-absorbed sample under the same raw material composition, preforming conditions and methylcellulose coating conditions.

[0073] Comparative Example 1

[0074] The preparation method of this comparative example is basically the same as that of Example 1, except that the iron-containing active component loading treatment in step (1) of Example 1 is not performed. In step (2), 55 g of expanded vermiculite without iron-containing active component loading treatment is used to replace 55 g of expanded vermiculite containing iron active component.

[0075] The resulting composite carrier was used to compare the changes in phosphorus removal rate and phosphorus enrichment per unit mass in water before and after the addition of iron-containing active components to expanded vermiculite.

[0076] Comparative Example 2

[0077] The preparation method of this comparative example is basically the same as that of Example 1, except that magnesium carbonate and citric acid are not added in step (3).

[0078] The resulting composite carrier was used to compare the changes in phosphorus removal rate and phosphorus enrichment per unit mass in water under conditions of adding pore-forming components and not adding pore-forming components.

[0079] Comparative Example 3

[0080] The preparation method of this comparative example is basically the same as that of Example 1, except that coconut fiber is not added in step (2).

[0081] The resulting composite carrier was used to compare the change in the mass retention rate on the sieve after 28 days of soaking under conditions with and without added coconut fiber.

[0082] Comparative Example 4

[0083] The preparation method of this comparative example is basically the same as that of Example 1, except that in step (5), after the calcium ion crosslinking is completed in the integrally molded carrier, the surface treatment is not performed using methylcellulose solution.

[0084] The cross-linked carrier was dried to constant weight under the same room temperature and ventilation conditions as in Example 1.

[0085] The resulting composite carrier was used to compare the changes in the mass retention rate on the sieve and the proportion of apparent extractable phosphorus after 28 days of immersion in the composite carrier under conditions of methylcellulose surface treatment and no methylcellulose surface treatment.

[0086] Comparative Example 5

[0087] The preparation method of this comparative example is basically the same as that of Example 5, except that this comparative example does not undergo calcium ion crosslinking treatment.

[0088] After removing the preform from the mold, it was not immersed in the calcium chloride solution. The preform without calcium ion crosslinking was cut into small pieces of similar size in the same manner as in Example 5, and then coated with a 1% (w / w) methylcellulose solution. The amount of methylcellulose solution coated was determined according to the same dry mass basis as in Example 5. After coating, it was allowed to stand for 30 min and then dried to constant weight under the same room temperature and ventilation conditions as in Example 5 to obtain the composite sample without calcium ion crosslinking.

[0089] The composite sample obtained in this comparative example was used to compare with Example 5 to evaluate the effect of calcium ion crosslinking on the soil phosphorus migration behavior of the sample after phosphorus uptake.

[0090] Comparative Example 6

[0091] The preparation method of this comparative example is basically the same as that of Example 1, except that in step (3), the amount of magnesium carbonate added is adjusted from 10 g to 25 g, and the amount of citric acid added is adjusted from 10 g to 25 g.

[0092] The resulting composite carrier was used to evaluate the effects of changes in the amount of pore-forming components added on the internal pore structure, water mass transfer capacity, and wet structure retention performance of the carrier, and to evaluate the changes in structural stability under excessive pore-forming conditions.

[0093] Comparative Example 7

[0094] The preparation method of this comparative example is basically the same as that of Example 1. The difference is that in step (3), magnesium carbonate and citric acid are not added, but 20 g of sodium chloride particles with a particle size of 100-300 μm are added as a pore-forming template.

[0095] After the calcium alginate crosslinking is completed, the resulting carrier is soaked in deionized water for 24 h to dissolve and remove the sodium chloride particles, thereby forming an internal porous structure.

[0096] The surface treatment was then performed in the same manner as in Example 1.

[0097] The resulting composite carrier was used to evaluate the effects of different pore construction methods on the carrier's phosphorus removal performance and structure retention performance.

[0098] Comparative Example 8

[0099] The preparation method of this comparative example is basically the same as that of Example 1, except that the iron-based active component loading treatment in step (1) of Example 1 is not performed. In step (2), expanded vermiculite without iron-based active component loading is used, and commercial iron hydroxyl oxide powder with the same mass as the iron-based active component content in Example 1 is added to directly mix the iron hydroxyl oxide with the expanded vermiculite.

[0100] The resulting composite carrier was used to evaluate the effects of different introduction methods of iron-containing active components on phosphorus capture performance and iron component stability.

[0101] Comparative Example 9

[0102] The preparation method of this comparative example is basically the same as that of Example 1, except that sodium alginate solution and calcium ions are not used to crosslink and form a continuous gel phase. 55 g of expanded vermiculite composite material loaded with iron-based active components, 15 g of coconut fiber, and an appropriate amount of deionized water are mixed evenly and then integrally molded by mechanical pressing.

[0103] Specifically, the mixture was placed in a mold and held at 10 MPa for 5 min to obtain a mechanically shaped composite carrier. This pressure condition ensures that the sample forms an integral structure and is used to compare the differences between non-gel fixation and gel continuous phase fixation methods.

[0104] The resulting composite carrier was used to evaluate the effects of different integral molding methods on the carrier's structural integrity and phosphorus removal performance.

[0105] Comparative Example 10

[0106] The preparation method of this comparative example is basically the same as that of Example 1, except that in step (2), coconut fiber is replaced with wood pulp fiber of equal mass.

[0107] The resulting composite carrier was used to evaluate the effect of different fiber reinforcement materials on the structure retention performance of the carrier after immersion.

[0108] Experimental Example 1

[0109] Evaluation of the phosphorus removal and enrichment performance of the composite carrier in water:

[0110] This experiment was used to evaluate the phosphorus removal and enrichment capacity of the composite carrier for phosphorus pollutants in water, and to compare the effects of iron-containing active components, internal pore structure construction methods, and changes in pore formation degree on the phosphorus removal performance of the composite carrier.

[0111] The composite carriers obtained in Examples 1, 2, 1, 2, 6, 7, and 8 were tested respectively. Comparative Example 1 was used to evaluate the effect of iron-containing active component loading on phosphorus capture performance; Comparative Examples 2 and 6 were used to evaluate the effect of changes in internal pore structure and pore formation degree on phosphorus removal performance; Comparative Example 7 was used to evaluate the effect of different pore construction methods on the performance of the composite carrier; and Comparative Example 8 was used to evaluate the effect of different iron-containing active component immobilization methods on phosphorus capture performance, and also to evaluate the effect of different iron-containing active component introduction methods on the stability of the iron component.

[0112] A simulated phosphorus-containing water body with an initial phosphorus concentration of 10 mg / L was prepared using potassium dihydrogen phosphate and deionized water.

[0113] Samples were taken from the middle of the dried carriers obtained in Examples 1, 2, 1 (Comparative), 2, 6, 7, and 8, respectively, and then cut or segmented into small pieces of similar size. The sampling location, size range, and drying state of the samples were kept consistent across all groups. Each group of carriers was dried to constant weight under room temperature and ventilation conditions before sampling and weighing.

[0114] Weigh 0.50 g of each sample and add them to 1000 mL of simulated phosphorus-containing water. Shake at 25 ℃ and 150 rpm for 24 h.

[0115] After shaking, the sample was separated from the solution, and the concentration of residual phosphorus in the solution was determined by ammonium molybdate spectrophotometry.

[0116] The phosphorus removal rate in water is calculated using the following formula:

[0117] η = (C0 - C e ) / C0×100% (1)

[0118] In formula (1):

[0119] η represents the phosphorus removal rate in water, expressed as % .

[0120] C0 represents the initial phosphorus concentration in the simulated phosphorus-containing water body, in mg / L.

[0121] C e The value represents the phosphorus concentration in the solution after shaking for 24 hours, expressed in mg / L.

[0122] Samples were taken from the composite carriers obtained in Examples 1, 2, 1, 2, 6, 7 and 8 respectively, using the same sampling method as the phosphorus removal rate test in water, and the weighing status of each group of samples was kept consistent.

[0123] The phosphorus enrichment per unit mass of sample is calculated using the following formula:

[0124] q = (C0 - C e )V / m (2)

[0125] In formula (2):

[0126] q represents the phosphorus enrichment per unit mass of sample, expressed in mg / g.

[0127] V represents the simulated volume of phosphorus-containing water, in L;

[0128] m represents the mass of the sample input, in grams.

[0129] Each group had 3 independent parallel samples, and the test results were expressed as mean ± standard deviation.

[0130] Table 1. Comparison of phosphorus removal performance and phosphorus resource enrichment capacity of different composite carriers

[0131]

[0132] Table 1 shows that Comparative Example 1, lacking the iron-containing active component, exhibited significantly reduced phosphorus removal performance, indicating that the iron-containing active component is a crucial component for phosphorus capture in the composite carrier. In Comparative Example 8, the introduction of the iron-containing active component via physical mixing resulted in lower phosphorus removal performance compared to Example 1, demonstrating that the method of immobilizing the iron-containing active component affects its utilization efficiency. The results of Comparative Examples 2, 2, and 6 indicate that the degree of pore formation affects the phosphorus removal performance of the composite carrier. Appropriately increasing the pore structure improves water entry capacity, while further increasing the pore formation degree failed to further enhance phosphorus removal. Comparative Example 7 demonstrates that different pore construction methods affect the performance of the composite carrier; the method of forming pores through the reaction of magnesium carbonate and citric acid in this invention achieves a better overall phosphorus removal effect.

[0133] Apparent density and 24-hour water absorption rate

[0134] To evaluate the effect of pore-forming components on the formation of internal pores and water ingress capacity of the composite carrier, the apparent density and 24-hour water absorption rate of the composite carriers obtained in Comparative Example 2, Example 1, and Example 2 were measured.

[0135] Composite carriers with similar shapes and sizes were selected for each group, with three independent parallel samples for each group. All samples were dried under the same room temperature and ventilation conditions until their mass stabilized, and the dried mass m of each sample was recorded. d .

[0136] The diameters d1, d2, and d3 of each carrier in three mutually perpendicular directions were measured using vernier calipers. Considering that the dried composite carrier may not be a perfect sphere, it was approximated as an ellipsoid, and its apparent volume was calculated using the following formula:

[0137] (3)

[0138] In formula (3):

[0139] V represents the apparent volume of the composite carrier, in cm³. 3 ;

[0140] d1, d2, and d3 are the diameters of the composite carrier in three mutually perpendicular directions, in cm.

[0141] The apparent density of the composite carrier is calculated according to the following formula:

[0142] (4)

[0143] In equation (4):

[0144] ρ is the apparent density of the composite carrier, in g / cm³;

[0145] m d The dry mass of the composite carrier is expressed in grams.

[0146] V represents the apparent volume of the composite carrier, in cm³. 3 .

[0147] Take separate dried samples from each group and accurately record the drying mass (m) before soaking. d Each sample was placed in a container containing 50 mL of deionized water and left to soak at 25 °C for 24 h.

[0148] After soaking, the sample was removed and placed on a sieve to drain for 60 seconds. Then, it was gently touched to the sample surface for 10 seconds using phosphate-free filter paper in the same manner to remove surface free water. The sample was not squeezed during the touching process. Immediately after treatment, the sample was weighed and its mass (m) after water absorption was recorded. w .

[0149] The 24-hour water absorption rate is calculated using the following formula:

[0150] (5)

[0151] In formula (5):

[0152] W represents the 24-hour water absorption rate of the composite carrier, expressed as % .

[0153] m w The mass of the composite carrier after soaking for 24 hours and removing surface free water is expressed in grams.

[0154] m d The dry mass of the composite carrier before immersion is expressed in grams.

[0155] The results of each group were taken as the average of three independent parallel samples and expressed as mean ± standard deviation.

[0156] Table 2 Macroscopic structural parameters and water absorption properties of composite carriers under different pore-forming conditions

[0157]

[0158] Table 2 shows that as the amount of pore-forming component added increases, the apparent density of the composite carrier decreases and the 24-hour water absorption rate increases, indicating that the pore-forming treatment reduces the macroscopic density of the carrier and improves its water absorption and inlet conditions. Combined with the results in Table 1, it can be seen that appropriate pore-forming is beneficial to improving the phosphorus removal and enrichment performance of the composite carrier, while excessive pore-forming may limit further performance improvement due to reduced structural integrity.

[0159] Apparent density and water absorption rate are only indirect indicators reflecting the macroscopic structure and water ingress capacity of the carrier, and are not used to limit the specific pore diameter, pore shape, porosity or connectivity of the internal pores.

[0160] Experimental Example 2

[0161] Evaluation of the quality retention performance of the composite carrier after immersion:

[0162] This experiment was conducted to evaluate the quality retention capability of the composite carrier after continuous immersion in an aqueous environment, and to compare the effects of the amount of coconut fiber added, the surface treatment of methylcellulose, the degree of pore formation, and the overall molding method on the quality retention performance of the composite carrier after immersion.

[0163] The composite carriers obtained in Examples 1, 3, 3, 4, 6, 9 and 10 were tested respectively.

[0164] Among them, Comparative Example 3 was used to evaluate the role of the reinforcing fiber structure, Comparative Example 10 was used to evaluate the influence of different fiber materials on the wet structure retention performance of the carrier, Comparative Example 4 was used to evaluate the role of the surface stabilizing layer, and Comparative Example 9 was used to evaluate the influence of the integral molding method on the wet structure retention performance of the carrier.

[0165] Composite carriers with similar shapes and sizes were selected for testing.

[0166] Each group of samples was dried at 60 ℃ until the mass stabilized, and the initial mass m0 before soaking was recorded.

[0167] Each group of samples was placed in a container containing 50 mL of deionized water and soaked continuously at 25 ℃ for 28 days. The soaking water was not changed during the soaking period.

[0168] Each group has 3 independent parallel samples.

[0169] After soaking, all carrier and detached portions from each container were transferred to a 5 mm mesh screen for sieving. The portion remaining on the screen was collected, dried at 60 °C until its mass stabilized, and then weighed and recorded as m. 28 .

[0170] The mass retention rate on the sieve after soaking is calculated using the following formula:

[0171] I = m 28 / m0×100% (6)

[0172] In formula (6):

[0173] I represents the mass retention rate on the sieve after soaking the composite carrier for 28 days, expressed as a percentage.

[0174] m0 represents the dry mass of the composite carrier before immersion.

[0175] m 28 The dry weight of the oversize portion obtained after soaking for 28 days and sieving is given.

[0176] Since this invention focuses on the overall recovery capability after long-term immersion, the retention rate of the mass on the sieve is used to evaluate the macroscopic integrity of the carrier.

[0177] Table 3. Sieve retention rates of different composite carriers after immersion for 28 days

[0178]

[0179] Table 3 shows that Comparative Example 3, without the addition of coconut fiber, exhibited a significantly lower mass retention rate after immersion, indicating that the fiber-reinforced structure helps improve the wet stability of the carrier. Comparative Example 10, using wood pulp fiber instead of coconut fiber, still showed some reinforcing effect, but its mass retention rate after immersion was lower than that of Example 1, indicating that the type of reinforcing fiber material affects the carrier's wet structure retention ability. In the system of this invention, coconut fiber and the calcium alginate gel continuous phase have a good synergistic reinforcing effect. In Comparative Example 6, the increased addition of pore-forming components, while beneficial for improving water penetration, reduced the integrity of the internal continuous structure of the carrier due to excessive pore structure, resulting in a lower mass retention rate after immersion. Comparative Example 9, using mechanical pressing to form an integral structure, had a lower 28-day mass retention rate than Example 1, indicating that mechanical pressing alone is insufficient to achieve stable maintenance of active components, fiber-reinforced structure, and porous structure. This invention, by fixing the internal components through the calcium alginate gel continuous phase, improves the wet stability of the carrier while ensuring the existence of the pore structure.

[0180] Experimental Example 3

[0181] Evaluation of the stability of the iron-containing active component:

[0182] This experimental example is used to evaluate the effect of different methods of introducing iron-containing active components on the stability of iron component fixation in composite carriers.

[0183] Composite carrier samples with similar shapes and sizes obtained in Example 1 and Comparative Example 8 were used for testing. The samples were soaked in deionized water for 28 days, the soaking solution was collected, and the iron concentration was determined by ICP-OES.

[0184] Table 4. Stability of iron release under different iron-containing active component immobilization methods

[0185]

[0186] As shown in Table 4, the amount of iron released after immersion in the composite carrier obtained in Example 1 is lower than that in Comparative Example 8. This indicates that preloading the iron-containing active components onto the surface and / or pore structure of the mineral carrier is beneficial to improving the fixation stability of the iron components in the composite carrier and reducing migration loss during the immersion process.

[0187] The above results are only applicable to the range of coconut fiber dosage used in this experiment, and the mass retention rate on the sieve is not equivalent to the compressive strength or other mechanical properties of the carrier.

[0188] Test Example 4

[0189] Evaluation of the apparent extractable phosphorus migration behavior of the composite carrier after phosphorus uptake in a simulated soil system:

[0190] This experiment was used to evaluate the migration behavior of phosphorus enriched in the composite carrier into the soil after phosphorus uptake and entry into a simulated soil system.

[0191] To avoid damaging the surface-treated area by cutting the carrier after the methylcellulose surface treatment is completed, the carrier is cut into small pieces of similar mass after the integrally molded carrier has completed calcium ion crosslinking, and then surface-treated and dried according to the methylcellulose solution concentration specified in Examples 1 and 4, respectively.

[0192] Comparative Example 4 used carrier blocks of the same size and mass range, without methylcellulose surface treatment.

[0193] (1) Comparison of surface treatment and formulation combination of phosphorus adsorption treatment of samples

[0194] Samples obtained from Example 1, Example 4, and Comparative Example 4 were selected respectively. The dosage of each group of samples was determined based on the preliminary test results, so that the initial phosphorus loading P0 of each group of samples before entering the soil system after phosphorus absorption was at the same or similar level, and the deviation between the average P0 of each group did not exceed 10%.

[0195] Simulated phosphorus-containing water with an initial phosphorus concentration of 50 mg / L was prepared using potassium dihydrogen phosphate and deionized water. The phosphorus concentration was expressed as P. Each group of samples was added to a container containing 50 mL of simulated phosphorus-containing water and shaken at 25 ℃ and 150 rpm for 24 h.

[0196] After shaking, the samples from Examples 1, 4, and Comparative Example 4 were removed from the solution, and the residual phosphorus concentration in the solution after phosphorus adsorption was measured. The samples were quantitatively rinsed with 10.0 mL of deionized water, and all rinsing solution was collected completely. The phosphorus concentration C in the rinsing solution was measured. w Avoid losing rinsing solution during rinsing; if dilution is required for measurement, include the corresponding dilution factor in the calculation. After rinsing, allow the sample to stand at room temperature for 10 minutes, then gently touch the sample surface with phosphorus-free filter paper until no obvious free water is visible; do not dry the sample.

[0197] The non-phosphorus-absorbed background sample was placed in 50 mL of deionized water and shaken at 25 °C and 150 rpm for 24 h. It was then treated using the same separation, quantitative rinsing, settling, and surface dehydration methods as the phosphorus-absorbed sample. Neither the phosphorus-absorbed sample nor the corresponding non-phosphorus-absorbed background sample was dried to minimize the impact of the drying process on the carrier structure and subsequent phosphorus migration behavior.

[0198] (2) Comparison of calcium ion crosslinking samples with phosphorus uptake treatment

[0199] Samples obtained from Example 5 and Comparative Example 5 were selected respectively, and the sample addition mass was adjusted according to the preliminary test results so that the initial phosphorus loading P0 of the two groups of samples after phosphorus absorption was at the same or similar level.

[0200] Each group of samples was placed into an inert nylon mesh bag measuring 1 cm × 2 cm with a pore size of 200 μm, with only one independent test sample in each bag. Preliminary tests confirmed that after shaking the Comparative Example 5 sample at 25 ℃ and 150 rpm for 24 h, no visible sample particles passed through the 200 μm nylon mesh bag. The mesh bag material did not release phosphorus under the test conditions and allowed water, phosphate, and soil solution to pass through freely. A blank control group with empty mesh bags was also established. Mesh bags from the same batch without samples were placed in 50 mL of simulated phosphorus-containing water at 50 mg / L and shaken under the same conditions for 24 h to evaluate the adsorption of phosphorus by the mesh bags. The phosphorus concentration change in the blank control group with empty mesh bags was below the detection limit of the assay method; therefore, no correction was made for the phosphorus adsorption amount of the empty mesh bags.

[0201] Example 5 and Comparative Example 5 used mesh bags of the same specifications and from the same batch, and the sealing method of the mesh bags was kept consistent.

[0202] The mesh bags containing the samples were added to 50 mL of simulated phosphorus-containing water with an initial phosphorus concentration of 50 mg / L, and shaken at 25℃ and 150 rpm for 24 h.

[0203] After shaking, the mesh bag was removed and quantitatively rinsed with 10.0 mL of deionized water, and the rinsing solution was collected completely. The actual initial phosphorus loading P0 of each sample was calculated based on the phosphorus concentrations in the solution before and after phosphorus absorption and the phosphorus concentration in the rinsing solution.

[0204] The samples from Example 5 and Comparative Example 5, corresponding to the non-phosphorus-absorbed background group, were placed in the same mesh bag and then placed in 50 mL of deionized water. They were shaken at 25 °C and 150 rpm for 24 h, and then subjected to the same rinsing and surface dehydration treatment as the phosphorus-absorbed samples.

[0205] (3) Calculation of initial phosphorus loading

[0206] The amount of phosphorus enriched in the test sample before it entered the simulated soil system was calculated using the following formula:

[0207] P0=(C0−C e )VC w V w (7)

[0208] In equation (7):

[0209] P0 represents the amount of phosphorus enriched in the test sample before it enters the simulated soil system, expressed in mg.

[0210] C0 represents the initial phosphorus concentration, in mg / L.

[0211] C eThe phosphorus concentration in the solution after shaking for 24 hours is expressed in mg / L.

[0212] V represents the simulated volume of phosphorus-containing water, in L;

[0213] C w The concentration of phosphorus in the rinsing solution is expressed in mg / L.

[0214] V w The volume of the rinsing fluid is 0.010 L in this experiment.

[0215] The actual P0 of each sample group was calculated before being introduced into the soil system. The initial loading mass of each sample group was adjusted through preliminary experiments to ensure that the P0 of different phosphorus-uptake sample groups were at the same or similar levels. The deviation between the average initial phosphorus loading of each group was controlled within 10%.

[0216] (4) Simulated soil culture and phosphorus extraction

[0217] The following experimental groups were set up, as shown in Table 5:

[0218] Table 5. Composition of composite carriers and experimental conditions for different experimental groups

[0219]

[0220] As shown in Table 5, the experimental groups were compared by adjusting factors such as the introduction method of iron-containing active components, pore-forming conditions, type of reinforcing fiber, and surface treatment method, in order to analyze the influence of different structural factors on the performance of composite carriers.

[0221] The same batch of soil was used for the experiment. The soil was air-dried naturally, and visible plant debris and stones were removed. It was then sieved through a 2.0 mm sieve. The equivalent of 5.00 g of dry soil was weighed and placed in a 100 mL covered culture container. The soil was gently compacted to form a stable culture layer.

[0222] For Examples 1, 4, and Comparative Example 4, the corresponding phosphorus-absorbing carriers or non-phosphorus-absorbing background carriers were directly added to the soil. For Examples 5 and Comparative Example 5, nylon mesh bags containing the corresponding carriers or composite samples were placed in the middle of the soil layer and covered with a small amount of culture soil to ensure full contact between the mesh bag surface and the soil. The specifications, burial depth, placement method, and contact area with the soil of the mesh bags used in each group of Examples 5 and Comparative Example 5 were kept consistent.

[0223] The water content of each culture system was adjusted to 60% of the maximum water holding capacity of the test soil using deionized water. The culture containers were placed at 25±1 ℃ under dark conditions, with the containers covered but gas exchange maintained. During the culture period, the soil was weighed every 2-3 days, and deionized water was added according to the mass loss to maintain the set soil water content.

[0224] Independent sampling groups were set up on days 7, 14, 28, and 56 of cultivation. Three independent parallel samples were set up for each treatment at each cultivation time point, and destructive sampling was performed after cultivation for the set time.

[0225] The proportion of extractable phosphorus from apparent NaHCO3 in soil

[0226] After the set incubation period, for Examples 1, 4, and Comparative Example 4, the composite carrier was removed from the culture soil using tweezers, and the soil adhering to the surface of the carrier was gently peeled off or brushed back into the original culture container. For Examples 5 and Comparative Example 5, the nylon mesh bag containing the carrier or composite sample was completely removed from the soil, and the soil adhering to the outer surface of the mesh bag was gently transferred back into the original culture container without squeezing or rinsing the mesh bag. Subsequently, all the soil after removing the carrier or mesh bag was used for NaHCO3 extraction.

[0227] Add 100 mL of 0.50 mol / L NaHCO3 extract (pH 8.5) to each portion of culture soil equivalent to 5.00 g of dry soil, and shake at 25 ± 1 ℃ and 180 rpm for 30 min. After shaking, centrifuge at 5000 rpm for 10 min, collect the supernatant, and determine the phosphorus concentration using the ammonium molybdate spectrophotometric method.

[0228] The amount of phosphorus that can be extracted from NaHCO3 measured on day t of cultivation is calculated according to the following formula:

[0229] P t =C t V e D (8)

[0230] In equation (8):

[0231] P t The amount of phosphorus that can be extracted from NaHCO3 in the simulated soil culture system at day t, expressed in mg;

[0232] C t This represents the phosphorus concentration in the supernatant, in mg / L.

[0233] V e The volume of the NaHCO3 extraction solution is in L.

[0234] D is the dilution factor during the measurement process; when undiluted, D=1.

[0235] To remove the extractable phosphorus background generated by the soil itself, as well as by the carrier, composite sample, or nylon mesh bag, each phosphorus-absorbed sample group was corrected for background using the corresponding non-phosphorus-absorbed sample group.

[0236] The soil blank group was used to monitor the change in extractable phosphorus from the soil itself over the incubation time; the formal background correction of each phosphorus-absorbing sample was performed using the corresponding non-phosphorus-absorbing sample incubation group, so as to simultaneously deduct the background influence generated by the soil itself, the carrier, composite samples or nylon mesh bags.

[0237] The extractable phosphorus content after background correction on day t is calculated according to the following formula:

[0238] ΔP t,soil =P t,吸磷 -P t,未吸磷 (9)

[0239] In equation (9):

[0240] ΔP t,soil The amount of phosphorus that migrated into the soil and could be extracted by NaHCO3 after deducting the background of the corresponding unabsorbed phosphorus sample at day t of cultivation is expressed in mg.

[0241] P t,吸磷 The amount of phosphorus that can be extracted from NaHCO3 was measured in the phosphorus uptake sample culture group, in mg.

[0242] P t,未吸磷 The amount of phosphorus that can be extracted from NaHCO3 is measured in mg for the corresponding non-phosphorus-absorbed sample culture group.

[0243] The proportion of phosphorus that can be extracted from the apparent NaHCO3 after culturing to day t is calculated according to the following formula:

[0244] R t,soil =ΔP t,soil / P0×100% (10)

[0245] In formula (10):

[0246] R t,soil The apparent proportion of phosphorus initially enriched in the test sample that migrated into the soil and was converted into an extractable form of NaHCO3.

[0247] ΔP t,soil The extractable phosphorus content of NaHCO3 after background correction is expressed in mg.

[0248] P0 represents the amount of phosphorus accumulated in the corresponding phosphorus uptake test sample before it enters the simulated soil system, expressed in mg.

[0249] Each sample was tested in three independent replicates at each incubation time point, and the results are expressed as mean ± standard deviation.

[0250] Table 6. Dosage and initial phosphorus loading of samples in each comparison group

[0251]

[0252] As shown in Table 6, the average initial phosphorus loading P0 deviation of each group of samples in the same comparison system was controlled within 10%, which provided a comparable basis for the subsequent comparison of soil phosphorus migration ratio.

[0253] Table 7. Effects of surface treatment and formulation combination on soil phosphorus migration.

[0254]

[0255] As shown in Table 7, the proportion of extractable phosphorus from apparent NaHCO3 in each group of soil increased with the extension of culture time. Comparative Example 4 was higher than Example 1 at all time points, indicating that methylcellulose surface treatment can reduce the proportion of phosphorus enriched on the carrier that migrates into the soil in the same culture time; Example 4 was lower than Example 1, indicating that the combination of sodium alginate concentration and methylcellulose concentration can further change this migration process.

[0256] Since Example 4 changed both the sodium alginate solution concentration and the methylcellulose solution concentration, this experiment could not determine the independent contribution of the two factors separately.

[0257] Table 8. Effects of calcium ion crosslinking on soil phosphorus migration

[0258]

[0259] As shown in Table 8, under the same conditions of raw material composition, preforming conditions, sample cutting method, methylcellulose coating standard and mesh bag culture conditions, the proportion of phosphorus that can be extracted from the soil surface NaHCO3 in Comparative Example 5 without calcium ion crosslinking was higher than that in Example 5 at each culture time point. This indicates that calcium ion crosslinking treatment can affect the migration process of phosphorus enriched in the sample into the soil. Example 5 showed a lower apparent migration ratio.

[0260] This comparison is only intended to illustrate the effect of calcium ion crosslinking on phosphorus migration behavior and is not intended to determine crosslinking density, internal pore size, or specific migration mechanisms.

[0261] It should be noted that Table 7 uses a culture method where the carrier is directly added to the soil, while Table 8 uses a culture method using nylon mesh bags for isolation. Therefore, the two tables are only used for comparing samples within their respective comparison systems, and no cross-sectional numerical comparisons are made between Table 7 and Table 8. This experiment does not involve evaluation of plant uptake, crop yield, fertilizer utilization rate, or actual fertilizer efficiency.

Claims

1. A fiber-reinforced porous phosphorus removal composite carrier, characterized in that, The device comprises a carrier body with internal pores and a surface treatment layer formed on the outer surface of the carrier body. The carrier body includes a calcium alginate gel continuous phase, expanded vermiculite containing iron active components, and coconut fiber. The calcium alginate gel continuous phase is used to fix the expanded vermiculite containing iron active components and coconut fiber into an integral carrier. The expanded vermiculite containing iron active components is dispersed and fixed in the calcium alginate gel continuous phase to capture phosphorus in the water. The coconut fiber is distributed in the calcium alginate gel continuous phase to improve the retention of the internal skeleton of the carrier after immersion. The internal pores are formed in the carrier body to increase the opportunity for water to enter the interior of the carrier and come into contact with the expanded vermiculite containing iron active components. The surface treatment layer is formed by treating the carrier body with a methylcellulose solution and drying it to reduce the loss of surface material of the carrier during immersion in an aquatic environment and to improve the overall morphological retention of the carrier after immersion.

2. The fiber-reinforced porous phosphorus removal composite carrier according to claim 1, characterized in that, The iron-containing active component is formed and loaded on the surface and / or pore region of expanded vermiculite; the iron-containing active component is formed by the reaction of an iron-containing precursor under alkaline conditions.

3. The fiber-reinforced porous phosphorus removal composite carrier according to claim 1, characterized in that, The continuous phase of the calcium alginate gel is formed by cross-linking sodium alginate with calcium ions; the calcium ions are provided by a calcium-containing cross-linking agent.

4. The fiber-reinforced porous phosphorus removal composite carrier according to claim 1, characterized in that, The internal pores are formed by the reaction of magnesium carbonate and citric acid to produce gas; the magnesium carbonate and citric acid react during the preforming and / or curing process of the carrier, causing pores to form inside the molded slurry.

5. The fiber-reinforced porous phosphorus removal composite carrier according to claim 1, characterized in that, The surface treatment layer is a methylcellulose surface treatment layer; the methylcellulose surface treatment layer is formed after the calcium ion crosslinking of the carrier is completed.

6. The fiber-reinforced porous phosphorus removal composite carrier according to claim 1, characterized in that, The composite carrier is an integral carrier that can be directly separated from the treated water body.

7. A method for preparing the fiber-reinforced porous phosphorus removal composite carrier according to claim 1, characterized in that, Includes the following steps: (1) Mix the iron-containing precursor with expanded vermiculite to form and load the iron-containing active component on the surface and / or pore area of ​​the expanded vermiculite. After solid-liquid separation, the expanded vermiculite containing the iron-containing active component is obtained. (2) Mix expanded vermiculite containing iron active components with coconut fiber, so that the coconut fiber is distributed in the mixture to obtain fiber-reinforced mixture; (3) Add sodium alginate solution, magnesium carbonate and citric acid to the fiber-reinforced mixture and mix to form a molding slurry; magnesium carbonate and citric acid react during mixing, preforming and / or curing to generate gas, thereby forming pores inside the molding slurry; (4) Place the molding slurry obtained in step (3) into a mold for pre-forming treatment to obtain a pre-formed body; place the pre-formed body into a calcium-containing cross-linking agent solution for cross-linking, so that sodium alginate forms a continuous phase of calcium alginate gel, and the expanded vermiculite, coconut fiber and internal pores containing iron active components are kept in the overall molding carrier. (5) The integrally molded carrier obtained in step (4) is surface treated with methylcellulose solution and then dried to form a methylcellulose surface treatment layer on the outer surface of the carrier, thereby obtaining the fiber-reinforced porous phosphorus removal composite carrier.

8. The method for preparing the fiber-reinforced porous phosphorus removal composite carrier according to claim 7, characterized in that, In step (1), the iron-containing precursor solution is adjusted to alkaline, and a dispersant and expanded vermiculite are added. After dispersion and heating reaction, the iron-containing active component is formed and loaded onto the expanded vermiculite. After the reaction is completed, the obtained solid is washed and dried to obtain expanded vermiculite containing the iron-containing active component.

9. A method for treating phosphorus-containing water, characterized in that, Includes the following steps: The fiber-reinforced porous phosphorus removal composite carrier described in claim 1 is placed in a phosphorus-containing water body, so that the phosphorus-containing water body enters the composite carrier and comes into contact with the expanded vermiculite containing iron active components, thereby capturing phosphorus in the water body; After treatment, the phosphorus-absorbed composite carrier is separated from the treated water.

10. A method for utilizing a composite carrier after phosphorus absorption, characterized in that, Includes the following steps: The composite carrier that has absorbed phosphorus using the method described in claim 9 is separated from the treated water body, and the separated composite carrier is added to the soil utilization system; The composite carrier that has absorbed phosphorus does not undergo special phosphorus desorption treatment or adsorbent regeneration treatment before entering the soil utilization system. The soil utilization system is used to facilitate the migration of phosphorus enriched in the composite carrier within the soil environment.